Herman and Chomsky’s Propaganda Model: Its Application on Electronic Media and Journalists in Pakistan - Syed Irfan Ashraf; Syed Hussain Shaheed Soherwordi; Tabassum Javed (Journal of Political Studies, 2016)
The political economy of media not only looks into power from ownership perspective but also explain news in top-down decision-making order. This paper is based on the application of Herman and Chomsky’s (1988) propaganda model to explain the privatization of media sector in Pakistan and the relationship of this unprecedented change to secondary and ground levels influences upon journalists working in a conflict zone. With the help of seven in-depth interviews with displaced tribal journalists reporting on the USled war-on-terror fought against militants in the northwestern Pakistan, this papers finds the model helpful in providing insight into macro-level developments i.e., commercialization of media and the concentration of media to serve interests of those ruling at the top. Weakness of the model, as the study finds, is the lack of vocabulary to use for micro-level developments, understanding and approach to develop insight into the social and cultural forces affecting media labor and influencing their working interests in reporting on a conflict zone. The outcome of this lack is, first, the absence of insight into decision-making dynamics between media elites and working journalists on the ground. Second, the element of working journalists’ resistance is not taken into account. On this account if macro-level analysis of the propaganda model could be held as strengths of the model, disconnect from ground realities is its weakness. And in order for political economy to connect with the bottom it is imperative for scholars to recognize and acknowledge those small details in which lays the element of resistance against power.